Rediscovering the way of Islamic propagation by continuing the tradition of religion-based agriculture - Miharja, Deni (HTS teologiese studies, 2022)
This study examines farming communities in Muslim villages that carry out one of the religious rituals in their agricultural cycle, namely tandur [planting rice seeds]. The study was then analysed with a theological analysis, namely Islamic theology, as the religion embraced by the community. The research method was carried out as follows: the researcher observed the research object in the Tanggulun Village of Subang Regency of West Java of Indonesia, where the case study was located. Researchers stayed at the research location and conducted interviews, supported by a voice recorder. The findings revealed that religious rituals performed by the farming community in the Muslim village, particularly during the agricultural cycle of planting rice seeds, gave rise to two types of tandur mantra. Such a religion-based culture does not conflict with the teachings of Islam as the religion of the farmers. The ritual represents local wisdom that the farming community can maintain and preserve theological and humanitarian elements inherited by Islamic da’wah [propagation] in the area. This study can show contemporary farmers the meaning of the mantra their parents used to chant. They can adapt whilst still honouring their religious heritage, even though the existing agricultural tools are relatively new.Contribution: This dissecting study of cultural narratives with theological studies can show that society still has traditions that can be maintained even in current conditions. Also, it opens the possibility of revealing local values in modern languages, so that there is a connection between past and present traditions. Disclosure of these values can be seen in the remaining culture, which is still practiced now, to enrich the study of ethnography, especially Sundanese ethnography. This is part of cultural science, which in this case is religious culture.